"Ed" Batchelder, captain of the baseball team, talks it over with Coach "Ken" Nash, n.d. - Munro, Melville S. (Tufts Archival Research Center, 2005)
5 x 5, mounted on 8 x 10 in: M. S. Munro, Miscellaneous pictures through the years, Vol. 1, p. 19